Pengaruh Kualitas Pelayanan dan Lokasi Usaha Terhadap Kepuasan Pelanggan di Restoran Quick Chicken Kota Jombang - Ayu Pujiyanti (BIMA : Journal of Business and Innovation Management, 2019)
This study aim to analyze the influence ofservice quality and business location partially and Simultaneouslyon customers satisfaction of Quick Chicken restaurant in Jombang by quantitative methode with questionnaire used as the instrument. The population in this research is customers that do transaction in Quick Chicken restaurant at Dokter Sutomo Street 9 Kepanjen, Jombatan, Jombang district, Jombang east java, zip code 61419. The sample is 130 respondens that founded by Incidental sampling technique. Multiple regression models were used to analyze the data. The results suggest that: (1) partially service quality has significant effect on customers satisfaction with t-count 9.072 > t-table 10.150 and significants rate 0,000. (2) partially business location has significant effect on customers satisfaction with t-count 5,417> t-table 0,171 and significants rate 0,000. (3) service quality and business location Simultaneously have significant effect on customers satisfaction with F-count 68.438> F-table 3,07 and significants rate 0,000.